2014
DOI: 10.1021/ci4004656
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding Mode Prediction by Docking: Mdm2/Mdmx Inhibitors as a Case Study

Abstract: The p53-binding domains of Mdm2 and Mdmx, two negative regulators of the tumor suppressor, p53, are validated targets for cancer therapeutics, but correct binding poses of some proven inhibitors, particularly the nutlins, have been difficult to obtain with standard docking procedures. Virtual screening pipelines typically draw from a database of compounds represented with 1D or 2D structural information, from which one or more 3D conformations must be generated. These conformations are then passed to a docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 77 publications
2
38
0
Order By: Relevance
“…However, the inter-molecular 1 H- 1 H NOEs were generally of lower intensity for the complexes with the SJ compounds versus that with p53-TAD1, suggesting that some of the small molecules do not bind as deeply within the hydrophobic groove of MdmX as does the p53 peptide. Our solution structures (Figure 3, Table 2) showed that the para-chloro-phenyl group of the SJ compounds bound within the pocket on MdmX that was occupied by W23 of p53-TAD1 (the “W23 pocket”) and that the adjacent substituent on the 4 position of the diazole ring ( e.g., meta-chloro-phenyl in SJ295) bound within the “L26 pocket” 13 (Figure 3). The substituents at this position in the different SJ compounds exhibited different patterns of inter-molecular NOEs but, in all cases, the numbers of NOEs were sufficient to uniquely position these moieties within the L26 pocket of MdmX.…”
Section: Resultsmentioning
confidence: 97%
“…However, the inter-molecular 1 H- 1 H NOEs were generally of lower intensity for the complexes with the SJ compounds versus that with p53-TAD1, suggesting that some of the small molecules do not bind as deeply within the hydrophobic groove of MdmX as does the p53 peptide. Our solution structures (Figure 3, Table 2) showed that the para-chloro-phenyl group of the SJ compounds bound within the pocket on MdmX that was occupied by W23 of p53-TAD1 (the “W23 pocket”) and that the adjacent substituent on the 4 position of the diazole ring ( e.g., meta-chloro-phenyl in SJ295) bound within the “L26 pocket” 13 (Figure 3). The substituents at this position in the different SJ compounds exhibited different patterns of inter-molecular NOEs but, in all cases, the numbers of NOEs were sufficient to uniquely position these moieties within the L26 pocket of MdmX.…”
Section: Resultsmentioning
confidence: 97%
“…NY2264 is an inhibitor targeting Myc, an IDP, and Myc-associated factor X (MAX) interaction [100]. Nutlin, an inhibitor of the p53-MDM2 interaction, binds to MDM2 and releases p53, which has a long IDR at its N-terminus [101, 102]. …”
Section: Intrinsically Disordered Proteins As Drug Targetsmentioning
confidence: 99%
“…The scoring function is used to evaluate the affinity between the receptor and the ligand for each conformation [20]. Scoring functions express the geometric complementarity and the energy strength of the interaction based on the physicochemical characteristics of the amino acids in contact with each other [21].…”
Section: Introductionmentioning
confidence: 99%